Solve for y 6a-3y=18

Math
6a-3y=18
Subtract 6a from both sides of the equation.
-3y=18-6a
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3y=18-6a by -3.
-3y-3=18-3+-6a-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3y-3=18-3+-6a-3
Divide y by 1.
y=18-3+-6a-3
y=18-3+-6a-3
Simplify each term.
Tap for more steps…
Divide 18 by -3.
y=-6+-6a-3
Cancel the common factor of -6 and -3.
Tap for more steps…
Factor -3 out of -6a.
y=-6+-3(2a)-3
Cancel the common factors.
Tap for more steps…
Factor -3 out of -3.
y=-6+-3(2a)-3(1)
Cancel the common factor.
y=-6+-3(2a)-3⋅1
Rewrite the expression.
y=-6+2a1
Divide 2a by 1.
y=-6+2a
y=-6+2a
y=-6+2a
y=-6+2a
y=-6+2a
Solve for y 6a-3y=18

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top